Inconsistencies in the Colombian Civil Service system (2014)
The Civil Service in Colombia exists because the state needs skilled workers for the performance of its duties towards the benefit of the citizens of a country. therefore the state becomes an employer, and one of the most desired ‘cos it enjoys of a good reputation in terms of job security and payment, but many things are ignored, especially regarding how to ascend and the rules regulating the system. This regulation seems to be unfair to some public officials who perform low fees and does not allow everyone to have the same opportunities to move up, which is supposed to be the purpose of the Career System.